2010
DOI: 10.1364/ol.35.002433
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of individual Raman Stokes lines in the visible regime using rectangular-shaped nanosecond optical pulses at 530 nm

Abstract: We demonstrate the selective excitation of individual Raman Stokes lines of up to the ninth order by pumping with rectangular-shaped optical pulses at 530 nm from a frequency-doubled adaptively pulse shaped fiber master oscillator power amplifier. We achieve extinction ratios of up to 15 dB between selected and adjacent Raman orders in a 1-km-long fiber.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…As seen in Fig.7, for both lengths of fiber, the spectrum appears much flatter than that of the first order Raman Stokes. This is very different from the discrete cascaded Raman lines observed in a 1km-long silica glass fiber [17]. We attribute such a continuum rather than discrete Raman Stokes lines here to (1) the much higher Raman gain coefficient and much broader Raman bands of tellurite glass compared to those of silica and (2) the nature of the multiple Raman peaks of tellurite glass.…”
Section: Generation Of Higher-order Raman Stokes and Antistokes Inmentioning
confidence: 56%
“…As seen in Fig.7, for both lengths of fiber, the spectrum appears much flatter than that of the first order Raman Stokes. This is very different from the discrete cascaded Raman lines observed in a 1km-long silica glass fiber [17]. We attribute such a continuum rather than discrete Raman Stokes lines here to (1) the much higher Raman gain coefficient and much broader Raman bands of tellurite glass compared to those of silica and (2) the nature of the multiple Raman peaks of tellurite glass.…”
Section: Generation Of Higher-order Raman Stokes and Antistokes Inmentioning
confidence: 56%
“…Selective excitation of Raman Stokes wavelengths can be realized by using a flat-topped rectangular pump pulse, since all points across the pulse experience identical Raman gain. Using this concept, selective excitation of individual Raman Stokes lines of up to the ninth order has been reported previously by our group [5]. However, it was found that with increased pump peak power, the suppression ratio of each excited Stokes line decreased and also the spectral bandwidths of the Stokes lines were broadened by other nonlinear effects.…”
Section: Introductionmentioning
confidence: 61%
“…Actually, some early studies on the wavelength conversion in visible or near-infrared region have verified that rectangular pulse was superior to promote pump energy transfer [21][22][23][24], comparing to Gaussian pump pulse. Since it offered the nearly consistent Raman gain across the temporal profile.…”
Section: Introductionmentioning
confidence: 99%